Childhood Immunization and COVID-19: An Early Narrative Review - Beric-Stojsic, Bojana; Kalabalik-Hoganson, Julie; Rizzolo, Denise; Roy, Sanjoy (Frontiers in Public Health, 2020)
The COVID-19 pandemic has evolved into arguably the largest global public health crisis in recent history – especially in the absence of a safe and effective vaccine or an effective anti-viral treatment. As reported, the virus seems to less commonly infect children and causing less severe symptoms among infected children. Hypotheses about cross-immunogenicity of existing childhood vaccines with the novel coronavirus have been offered. This narrative review provides an inclusive view of scientific hypotheses, logical derivation, and early analyses that substantiate or refute such conjectures. At the completion of a relatively less restrictive search of this evolving topic, thirteen articles – all published in 2020, were included in this early narrative review. Directional themes arising from the identified literature suggest the potential relationship between childhood vaccination and COVID-19 – either based on the potential genomic and immunological protective effects of heterologous immunity, or based on observational associations of cross-immunity among vaccines and other prior endemic diseases. Our review suggests that immune response to the SARS-CoV-2 virus in children is different than in adults, resulting in differences in the levels of severity of symptoms and outcomes of the disease in different age groups. Further clinical investigations are warranted of at least three childhood vaccines: BCG, MMR and HEP-A for their potential protective role against the SARS-CoV-2 virus.